PP.12.08: THE EFFECT OF HEAD AND NECK RADIOTHERAPY ON BLOOD PRESSURE AND ORTHOSTATIC HYPOTENSION IN PATIENTS WITH HEAD AND NECK TUMORS. (June 2015) - Leibowitz, A.; Sharabi, Y.; Grossman, E.; Levartovsky, M.; Appel, S.; Gluck, I.
Abstract : Objective: Head and neck cancer (HNC) is the sixth most common cancer worldwide. Radiotherapy (RT) plays a key role in the management of HNCs, especially in locally advanced disease. There is a notion that patients undergoing head and neck RT, especially elderly ones, are suffering from low and labile blood pressure (BP) during the treatment. They complain of weakness and fatigue and are prone to recurrent falls. The aim of this study was to characterized BP changes during RT period. Design and method: Patients with HNC, recieving radiation to the neck for a total dose of 45–70 Gy, with Performance status (Karnofsky) 0–2 were recruited from the Chaim Sheba Medical Center RT unit. Office BP, including orthostatic measurements and 24H ambulatory BP (ABPM) were measured at baseline and after 30 days of therapy. Results: 15 patients (13 males), 68 ± 11 years old were recruited between May 2013 and Novembers 2014. 7 hypertensive patients continued their antihypertensive treatment during the study. Office systolic BP (SBP) but not diastolic BP (DPB) decreased significantly after 30 days (SBP: 133 ± 5 to 126 ± 4 mm Hg; p < 0.05, DBP: 79 ± 4 to 76 ± 4 mm Hg; P = NS) without a significant change of heart rate. Analysis of 24H ABPM confirmed the decrease in SBP and showed a significant decrease also in DBP. Average 24H BP levels decreased from 134 ± 4/78 ± 2 to 126 ± 4/72 ± 3 mm Hg; P < 0.01. A similar trend was observed for day and night BP levels. During the first month of treatment 2 patients fall. No orthostasis was observed after 30 days of treatment. Conclusions: There is a significant BP reduction after 30 days of head and neck RT, without orthostatic changes. More studies should be done to evaluate the mechanism of this BP reduction and the association with patients' complains.